2020
DOI: 10.3171/2020.5.focus20255
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative bone health assessment and optimization in spine surgery

Abstract: OBJECTIVEThe purpose of this investigation was to characterize the bone health in preoperative spine surgery patients. This information will provide a framework to understand the needs and methods for providing bone health optimization in elective spine surgery patients.METHODSA retrospective study of 104 patients undergoing bone health optimization was performed. Patients were selected based on risk factors identified by the surgeon and suspected compromised bone health. Evaluation included history and examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…have used preoperative corticosteroids [10]. These depictions (4.61%, 95% confidence interval [CI], 4.36 -4.86) of the population was on preoperative steroids, and 1469 (5.52%; 95% CI, 5.24 -5.79) were followed by postoperative complications [11].…”
Section: Resultsmentioning
confidence: 99%
“…have used preoperative corticosteroids [10]. These depictions (4.61%, 95% confidence interval [CI], 4.36 -4.86) of the population was on preoperative steroids, and 1469 (5.52%; 95% CI, 5.24 -5.79) were followed by postoperative complications [11].…”
Section: Resultsmentioning
confidence: 99%
“…4 A major limitation in spine surgery patients is that arthritis and degenerative scoliosis increase DXA-measured BMD. Anderson et al 6 reported that the spine T-scores were 1.5 × higher than the hip in spine patients. Another limitation of DXA is that the T-score criteria has low sensitivity as the majority of patients having low-energy fractures have T-scores > −2.5.…”
Section: Definition Of Osteoporosismentioning
confidence: 98%
“…11,12 Previous literature has demonstrated rates of osteoporosis in ASD as high as 32.8%, with only 34.4% of those patients receiving treatment. 12,13 Osteoporosis is a well-established risk factor for complications after spinal fusion, including proximal junctional kyphosis, pseudoarthrosis, fracture, and revision surgery. [14][15][16][17] Given the high rate of osteoporosis in ASD patients, the criteria for screening for osteoporosis have been challenging and expanded to increase sensitivity.…”
Section: Osteoporosis and Bone Mineral Densitymentioning
confidence: 99%